Recycled polyester geosynthetic influence on improvement of road and railway subgrade bearing capacity— Laboratory investigations - Malicki, Konrad (2022)
After years of using geosynthetics in civil engineering and infrastructure construction, it has recently become necessary to consider the possibility of recycling and reusing these materials. This paper presents the results of laboratory tests of the effect of recycled geogrid on the bearing capacity of soils using a CBR test. A polyester geosynthetic was selected for testing due to its high resistance to biodegradation and wide application. In a series of laboratory tests, two types of road and railway subgrade were used, mixed with geosynthetic cuttings in two different weight concentrations. The aim of the research was to demonstrate whether old demolition geosynthetics could be used to strengthen road and rail subgrade as recycled material. The influence of the geosynthetic cutting shape was also considered. The obtained results confirm the possibility of using recycled geogrid to improve the bearing capacity of the pavement subgrade, at least under these laboratory conditions. In the case of sand, the use of 2.0% additive causes that the poorly compacted soil obtains sufficient bearing capacity for the layer of road improved subgrade. As expected, the level of this improvement depends on the type of soil and the shape of geogrid cuttings.